2016
DOI: 10.1002/prep.201600086
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Behind‐Plate Overpressure Effect by Reactive Material Projectile

Abstract: The behind‐plate overpressure effect by a reactive material projectile with a density of 7.7 g cm−3 was investigated by ballistic impact and sealed chamber tests. The reactive projectile was launched onto the initially sealed test chamber with a 2024‐T3 aluminum cover plate with a thickness of 3 mm, 6 mm, and 10 mm, respectively. Moreover, the overpressure signals in the test chamber were recorded by a pressure sensor and a data acquisition system. The experimental results show that the behind‐plate overpressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Reactive materials, also known as impact-initiated energetic materials, are designed to release a large amount of energy under highly dynamic load. 1,2 In various military settings, such materials are used to replace those components usually made out of inert materials, such as fragment warheads, shaped charge warheads, penetrating warheads and projectiles. In addition to kinetic energy attack and the physical damage caused to the target, reactive materials can also cause a comprehensive killing effect such as explosion shock, overpressure, and ignition.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive materials, also known as impact-initiated energetic materials, are designed to release a large amount of energy under highly dynamic load. 1,2 In various military settings, such materials are used to replace those components usually made out of inert materials, such as fragment warheads, shaped charge warheads, penetrating warheads and projectiles. In addition to kinetic energy attack and the physical damage caused to the target, reactive materials can also cause a comprehensive killing effect such as explosion shock, overpressure, and ignition.…”
Section: Introductionmentioning
confidence: 99%
“…Active material, also known as reactive material, is a typical impact initiation energetic material [ 1 , 2 , 3 ], which is composed of at least two kinds of nonexplosive materials. Due to the unique mechanical and chemical properties of the active materials [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], it has high application values in military fields such as air defense, antimissile barrier breaking and so on. Distinct from the traditional inert damage elements such as tungsten and steel alloy, which rely on a single kinetic energy to hit the target, the damage element made of active materials produces high temperature combustion and explosion effects when hitting the target at high speed and releases a large amount of chemical energy quickly, causing more damage to the target.…”
Section: Introductionmentioning
confidence: 99%
“…Herbold's [17] research indicated that the increase of the size of W particles promoted the reaction of Al-PTFE composites. Using a sealed chamber, Xu [18] conducted a series of ballistic experiments to investigate the influence of impact velocity on the energy release characteristics of a PTFE-Al-W reactive material projectile. The results show that the reaction efficiency increases with increasing impact velocity.…”
Section: Introductionmentioning
confidence: 99%